KOHESI GRAMATIKAL: KAJIAN KEUTUHAN WACANA TUGAS MAHASISWA PENDIDIKAN BAHASA DAN SASTRA INDONESIA, FAKULTAS BAHASA DAN SASTRA, UNIVERSITAS NEGERI MAKASSAR - Azis Azis; Juanda Juanda (Fakultas Sastra Universitas Negeri Malang, 2017)
Abstract: This study aims to elaborate on the use of grammatical cohesion student assignment. The research method is content analysis. Data source is the text contained in the student assignment Indonesian Language and Literature Education. The data in the form of grammatical cohesion. Data analysed with the method content analysis. The results showed that: first, the pronouns. The use of pronouns we and they are often used in stringing sentences students conducted again. Second, the substitution. Substitution that occurs in the tasks students are generally limited to the replacement of the word or group of words with pronouns. Third, the elepsis. Elepsis in student assignments sometimes occur due to the removal of appropriate words must be present in the sentence. Fourth, conjunctions. Conjunctions are used in student writing right there and some are not appropriate. This is caused by a lack of understanding of student use of conjunctions Permalink/DOI: dx.doi.org/10.17977/um015v45i22017p170